Intercommunication of anthropometric indexes and physical capabilities of children 4-6 years in prognostication of sporting results in a gymnastics - Pomazan А.А (Kharkov National Pedagogical University, 2010)
Problems and questions which are related to the process of selection of children (boys) 4-6 years in the groups of initial preparation for employments by a sporting gymnastics are considered. Materials of the last publications are analyzed on this theme. The results of correlation anthropometric data and indexes of level of development of physical capabilities of children of this age group analysis are resulted in the article, with the purpose of determination of their perspective to employments by sport. More informing is certain for a selection to employments by a gymnastics morphological indexes of children of preschool age.